Mattos, Hebe Maria. Das cores do silêncio: os significados da liberdade no Sudeste escravista, Brasil século XIX. 2ª ed., Rio de Janeiro, Nova Fronteira, 1998. 379p. - Florence, Afonso Bandeira (Afro-Ásia, 1998)
.